Implementación de una máquina cortadora de chips de neumáticos fuera de uso - Agila Aguinda, Geovanna Shirley (2022)
For this research project, it is proposed to design and "Implement a tire chip cutting machine out of use" in order to reduce environmental pollution, recycle and reuse discarded tires. In this way, the implementation of this machine through mobile and fixed blades and through a mechanical process makes small cuts of rubber pieces with established measures, which thus allows the feasibility of subsequent processes. The necessary information for the investigation and execution of the project was used scientific references as bibliographical antecedents on rubber cuts that are described in the theoretical and methodological foundation, being in these chapters where the factors that influence and the diverse components that are indispensable are described. for the construction of the machine, because the result obtained has various processes within the mechanical and industrial field. Once the design of the parts that constitute the machine has been carried out, its characteristics are verified through the calculations and the plans of each of the pieces made in the Autodesk Inventor software program that verifies the simulation values through finite elements. This tire chip cutting machine was built for the benefit of the students of the Electromechanical Engineering Career of the Technical University of Cotopaxi-La Maná Extension, being of great help to strengthen their practical and theoretical knowledge.